Utilizing Liquid Crystals for Environmentally-Friendly Smart Coatings and Eco-Composites: Materials, Mechanisms, and Applications - Shaban, Hassanein (New Environmentally-Friendly Materials, 2026)
Liquid-crystalline (LC) materials—traditionally known for displays—are now emerging as sustainable functional materials. In particular, plant-derived LCs (cellulose nanocrystals, hydroxypropyl cellulose, etc.) and bio-based polymer networks can form biodegradable, stimuli-responsive coatings and eco-friendly composites. Recent advances have enabled green synthesis of LCs using waste biomass (e.g., converting agricultural or forestry residues into Hydroxypropyl Cellulose (HPC) or cellulose nanocrystals (CNC)) and solvent-free multicomponent reactions that avoid harmful volatile organic compounds (VOCs). These bio-LCs can be formulated into VOC-free coatings (e.g., waterborne polymer-dispersed LCs, Ultraviolet (UV)-curable LC networks) and infused with peptides or natural microgels to yield switchable antimicrobial/antifouling surfaces. Hybrid composites combining LCs or LC polymers with plant fibers (hemp, flax, wood pulp) produce lightweight, recyclable panels with high acoustic damping and thermal insulation. For example, a sandwich panel made from natural fiber cores achieved low thermal conductivity (~2.75 mW/m·K) and strong mid-frequency sound absorption. Performance metrics such as tensile strength (e.g., CNC–silk fibers reaching ~300 MPa), acoustic absorption, and microbial kill-rates are encouraging. Lifecycle analyses emphasize biodegradability and recyclability: many cellulose-based LCs degrade in weeks, and green panel materials avoid toxic additives. However, challenges remain in scaling up, ensuring stability (e.g., against moisture), and integrating LC fabrics with building standards. Future research is directed toward high-efficiency manufacturing, multimodal responsiveness (light, heat, bio-signals), and lifecycle engineering to fully realize LCs in sustainable materials.